Linguistic and Stylistic Features of Literary Works and Texts of Literary Criticism by Oksana Luschevska (Linguostylistic Studies, 2016)
The article highlights the ways and means of implementing linguistic and stylistic content in the fiction and literary studies texts by Oksana Luschevska. The creative heritage of the Ukrainian diaspora representatives is an interesting domain for revealing the issue of how a person affects the language and how language affects the individual, his/her thinking, mentality and inner culture. In the process of creating a literary text Oksana Luschevska employs the Ukrainian language as the principal tool for verbalization of the plot ideas development and the emotions of the protagonists. Analytical interpretation of the literature for children is performed within the theoretical framework of literary criticism, linguistic and extra-linguistic experience of the author, stimulated by the motives of her activities and communicated in English. Linguistic personality of the writer and a researcher of the children’s literature is characterized by the following features: bilingualism, multiculturalism, transculturalism, intercultural synthesis of various philosophical views, cultural, artistic and literary criticism practices. Key words: bilingualism, linguistic analysis, literature for children, language personality, style. References